PENGEMBANGAN KAPASITAS SDM UNTUK MENINGKATKAN EFISIENSI DAN EFEKTIVITAS BUMDES DI DESA BIAK KECAMATAN LUWUK UTARA KABUPATEN BANGGAI - Saudin, La (Yayasan Education and Social Center, 2025)
This study aims to determine the development of human resource capacity to improve the efficiency and effectiveness of Village-Owned Enterprises (BUMDes) in Biak Village, through improving the quality of human resources. The role of BUMDes is very significant in improving community welfare. BUMDes acts as the main driver in developing local economic potential at the village level. This research method is carried out with a qualitative analysis approach and adding simple quantitative analysis, the data used in this study is primary data taken directly from the key person who has been determined in this study so that it can provide representative decision results. The results of this study can be explained that improving the quality of human resources is the main component in the development of BUMDes in Biak Village, Banggai Regency. While improving human resources in the development of BUMDes in Banggai Regency can be done through increasing capacity and innovation through education and training followed by education, knowledge and experience. Thus, improving the quality of human resources in the development of BUMDes in Banggai Regency can prioritize increasing capacity and innovation. The results of this study can provide empirical benefits as a basis for policies carried out for the development of BUMDes which can be carried out by prioritizing the improvement of human capital as one of the most important aspects in efforts to develop BUMDes by increasing the capacity and innovation of BUMDes management, education, knowledge and experience possessed by BUMDes actors, this study has limitations that the analysis used can only focus on the development of BUMDes Biak Village in Banggai Regency.